2022
DOI: 10.3389/fimmu.2022.898498
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine levels are associated with tumor progression during FOLFIRINOX chemotherapy and overall survival in pancreatic cancer patients

Abstract: BackgroundBiomarkers predicting treatment response may be used to stratify patients with pancreatic ductal adenocarcinoma (PDAC) for available therapies. The aim of this study was to evaluate the association of circulating cytokines with FOLFIRINOX response and with overall survival (OS).MethodsSerum samples were collected before start and after the first cycle of FOLFIRINOX from patients with PDAC (n=83) of all disease stages. Overall, 34 circulating cytokines were analyzed with a multiplex immunoassay. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In the meantime, a combination of immunotherapy and other therapeutic agents may be able to reverse the malignant process to some extent while improving the quality of life and survival of cancer patients. Some studies have also suggested that IL-7-based therapy may improve the prognosis of patients, but this idea still needs to be evaluated in more in-depth studies in the future [ 132 ]. The tumour microenvironment is a crucial factor in the development, progression, and prognosis of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, a combination of immunotherapy and other therapeutic agents may be able to reverse the malignant process to some extent while improving the quality of life and survival of cancer patients. Some studies have also suggested that IL-7-based therapy may improve the prognosis of patients, but this idea still needs to be evaluated in more in-depth studies in the future [ 132 ]. The tumour microenvironment is a crucial factor in the development, progression, and prognosis of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…This includes both local cellular immunity responses and systemic soluble mediator networks 35 38 . Furthermore, increasing evidence supports the evaluation of cell markers and immune mediators as predictors of response to treatment or mechanisms of disease development 39 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an analysis of active cytokines in an individual’s cancer microenvironment or tissues during chemotherapy, especially in comparison to the pre-intervention levels or activities, could reveal information about the biological mechanisms operating in the tumor under therapy stress. Such cytokine readouts may correlate with patient clinical outcomes [ 47 , 48 , 49 , 50 ]. Since cytokines are readily detectable in tissue fluids, this approach to precision medicine has an added value for clinical monitoring and decision making.…”
Section: Cytokine Responses In Solid-tumors Therapy: An Emerging Them...mentioning
confidence: 99%